A junior doctor's experience of critical illness: from treating patients to becoming a patient with COVID‐19. Issue 1 (10th June 2020) - Ramachandran, S.
Summary: When the coronavirus disease 2019 (COVID‐19) pandemic was declared, it was clear that severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) would have far‐reaching impacts on medicine, society and everyday life. As a junior doctor working closely with patients with SARS‐CoV‐2 infection, I was aware of my personal risk of exposure to the virus. I assumed that as a fit and well 26‐year‐old with no comorbidities, if I were to become infected, it was unlikely that COVID‐19 would be severe. However, I became critically unwell following a week of clinical work, necessitating hospital admission, tracheal intubation and mechanical ventilation. I remained mechanically ventilated for 6 days and was then transferred to a medical ward 2 days later. After two further days of rehabilitation, I was discharged home. This reflection is not a junior doctor's view of how COVID‐19 was managed by the NHS, but a personal view of my illness from 'the other side of the curtain'. My reflections focus upon the psychological aspects of my experiences, exploring the memories that I formed around the time of critical care, how the fears that I possessed were managed with exceptional communication, and the importance of the wider healthcare team in my recovery.